Gender trends in match rate to surgical specialties in Canada: A retrospective study from 2003-2022. - Mostafa Bondok; Mohamed S Bondok; Anne Xuan-Lan Nguyen; Christine Law; Nawaaz Nathoo; Nupura Bakshi; Nina Ahuja; Karim F Damji (PLoS ONE, 2024)
Background In Canada, there is a recognized underrepresentation of women in the field of surgery. However, the extent to which this trend applies across various surgical specialties is not well delineated. The aim of this study is to identify existing disparities and trends over time to inform the need for future interventions to make the match process more equitable for applicants. Methods Data regarding surgical specialty applicants was extracted from the Canadian Resident Matching Service (CaRMS)'s 2003 to 2022 reports. Results A total of 9,488 applicants ranked surgical specialties as their first choice from 2003-2022. Increases in the proportion of women applicants comparing periods 2003-2007 to 2018-2022 were significant for cardiac surgery (22% to 43%, p = 0.03), general surgery (46% to 60%, p<0.001), orthopedic surgery (23% to 35%, p<0.001), urology (23% to 38%, p<0.001), and all aggregated surgical specialties ('all surgery') (45% to 55%, p<0.001). An increase in the proportion of women applicants who matched over the same periods was observed for general surgery (+47% to 60%, p<0.001), orthopedic surgery (24% to 35%, p<0.01), urology (21% to 34%, p<0.001), and all surgery (46% to 54%, p<0.001). From 2003-2022, a lower match rate for women compared to men was observed for otolaryngology (0.60 v 0.69, p = 0.008), urology (0.61 v 0.72, p = 0.003), and all surgery (0.71 v 0.73, p = 0.038), while higher match rates were observed for ophthalmology (0.65 v 0.58, p = 0.04). No statistically significant differences in match rate were observed from 2018-2022. Conclusions While the proportion of women applicants to surgical specialties in Canada has been increasing, women remain underrepresented in several surgical specialties. This underrepresentation cannot be solely attributed to fewer women applying to these specialties, as women experience lower success rates when matching to specific surgical specialties. Further research is essential to identify and address the underlying causes of these disparities.